Peran Guru sebagai Supervisor Pendidikan dalam Meningkatkan Mutu Madrasah - Ahyani, Edi; Dhuhani, Elfridawati Mai (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to examine the role of teachers as educational supervisors in improving school quality, with a focus on a case study at MTs Al-Mukhlasin Ambon. Teachers not only serve as instructors in the classroom but also have a strategic function in nurturing, monitoring, and evaluating the learning process. Through a descriptive qualitative approach, data was collected through observation, in-depth interviews, and documentation of teachers, madrasah principals, and learning materials at the school. The data analysis technique uses the Miles and Huberman model which includes three main stages: data reduction, data presentation, and drawing conclusions. The research findings indicate that teachers at MTs Al-Mukhlasin are beginning to engage in informal academic supervision, such as providing feedback to each other on teaching methods, teaching materials, and the performance of their colleagues. This supervisory activity contributes to improved professional competence, the development of more innovative teaching methods, and the creation of a collaborative culture within the school environment. Despite some remaining challenges such as time constraints and the absence of a structured supervision system, teachers' active participation in supervision practices has proven capable of driving improvements in the teaching and learning process and enhancing student learning outcomes. This study recommends the need for school policies that support collaborative supervision, supervisory skills training for teachers, and technology integration to strengthen reflective practice and ongoing professional development.